BANGUNAN PERTAHANAN (LOUVRAK) JEPANG DI PULAU DOOM - Sri Chiirullia Sukandar (BALAI ARKEOLOGI PAPUA, 2013)
The outbreak of the Pacific War between Japan and the Allied forces occur over Japan’s ambition to become one Superpower in Asia. Papua is located in the Pacific waters are also at infasi Japan to dominate Asia. Doom Island is located in the western part of New Guinea became one of the regions that have successfully mastered. method used was a descriptive survey method. The purpose of this paper to describe the various forms of Japanese defense building in Doom Island, as well as trying to be able to explain the role of the defense buildings during the fighting around the Island of Doom. Japanese troops on the island to build military facilities in the form of holes defense to attack alliedfleets in the waters of the Pacific.AbstrakPecahnya perang pasifik antara Jepang dengan pasukan Sekutu terjadi atas ambisi Jepang untuk menjadi salah satu Negara Adidaya di Asia. Tanah Papua yang terletak di perairan Pasifik pun tidak terlepas dari infasi Jepang untuk menguasai Asia. Pulau Doom yang terletak di bagian barat Pulau Papua menjadi salah satu daerah yang berhasil dikuasainya. metode yang digunakan adalah metode survei dan bersifat deskriptif. Tujuan tulisan ini untuk mendeskripsikan berbagai macam bentuk bangunan pertahanan Jepang di Pulau Doom, serta berusaha untuk dapat menjelaskan peranan bangunan-bangunan pertahanan tersebut selama terjadinya pertempuran di sekitar Pulau Doom. Di pulau ini pasukan Jepang membangun sarana militer berupa lubang pertahanan untuk menyerang armada laut sekutu di perairan pasifik.